家庭資源、學習態度、多元入學管道與學習成效關聯性之研究：以臺灣某大學為例 Relationships Among Family Resources, Learning Attitudes, University Admission Channels, and Learning Performance: Case of a Taiwanese University - 黃政仁 Cheng-Jen Huang; 黃偉婷 Wei-Ting Huang (National Taiwan Normal University, 2017)
本研究主要目的在探討家庭資源、學習態度、多元入學管道與學習成效之間的關係。研究對象主要是個案大學的大一學生，並控制學生之背景變數，建構以家庭資源為自變數，學習態度、多元入學管道與學習成效為依變數的廣義結構方程模型。有別於過去的研究，本研究將學習成效分為智育及服務學習之學習成效，且智育之學習成效包含較具客觀性的會考成績。研究結果顯示，家庭資源愈豐富，學生智育與服務的學習成效反而愈差。其次，家庭資源愈豐富的學生傾向於選擇甄選入學管道。最後，學生的學習態度愈佳，則無論智育或服務之學習成效也會愈好。 This study analyzed the interrelationships between family resources, learning attitudes, university admission channels, and learning performance. This study used first-year college students enrolled at the case university as the research sample. This research applied the generalized structural equation model and used family resources as its independent variable and learning attitude, university admission channels, and learning performance as dependent variables. Learning performance was separated into intellectual and service learning performance. The empirical results indicated that students with more family resources were less likely to exhibit high intellect and high service learning performance. In addition, students with more family resources were more likely to enter the university through recommendations and screening. Finally, students with superior learning attitudes were more likely to exhibit high intellect and high service learning performance.